Implementasi Kebijakan Standar Pelayanan Minimal (Spm) Kesehatan Pada Pelayanan Kesehatan Lanjut Usia (Lansia) Di Kota Padang - Viqda Vina Lucyianaa; Hendri Koeswara; Roni Ekha Putera (JIAP (Jurnal Ilmu Administrasi Publik), 2023)
This research discusses the Implementation of the Minimum Service Standards (MSS) Policy on Elderly Health Services in Padang City. SPM are provisions regarding the type and quality of basic services which are mandatory government affairs that every citizen has the right to obtain at a minimum. There are 6 areas of basic service affairs related to SPM, one of which is the SPM Health sector. For Health SPM, there are 6 health services, one of which is elderly health services. In 2020 there was a Covid-19 pandemic, so people had difficulty getting health services that met the standards at health facilities. Therefore, the purpose of this research is to find out how the Implementation of SPM Health Policy on Elderly Health Services in Padang City. This research is a descriptive qualitative research with data collection techniques in the form of observation, interviews, and documentation. The results of this study are the performance of the Health SPM Policy Implementation on Elderly Health Services in Padang City when analyzed using the Implementation theory by Van Metter and Van Horn on the variables of policy standards and objectives, characteristics of implementing agents, and attitudes / tendencies of policy implementers have been carried out in accordance with the objectives of the policy. However, the variables of resources, communication between implementing organizations and the social, economic and political environment have not run optimally in accordance with the expected objectives of the Health SPM policy